1979
DOI: 10.1002/ajpa.1330510107
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal differentiation of Macaca fascicularis and Macaca nemestrina in relation to arboreal and terrestrial quadrupedalism

Abstract: Sympatric Macaca fascicularis and M. nemestrina of Borneo coexist, in spite of similar frugivorous diets, by occupyimq habitats that differ in density of food sources. A primary specialization for I-raging on widely dispersed food sources is terrestrial travel by M. nemestrina, in contrast t o arboreal travel by M. fascicularis in the richer habitat. Theoretical biomechanical demands of terrestrial and arboreal quadrupedalism suggest the hypothesis that M. fascicularis should be built like a powerful climber a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
1
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(143 citation statements)
references
References 26 publications
6
135
1
1
Order By: Relevance
“…However, there is potential confusion over the relationship between habitat and/or locomotor preference and olecranon length. It has been argued that more terrestrial monkeys have shorter olecranons than do arboreal species [23,44,49], but in the present study, this trend is reversed, with 'forest arboreal' specimens having relatively short olecranons, in contrast to the longer olecranons of the 'open mixed' and 'open terrestrial' specimens, as well as T. oswaldi (tables 13, 16). To investigate this further, olecranon length was divided by both ulna length (OLUL) and ulna length minus styloid process length (OLUL2) (table 16).…”
Section: Eltoncontrasting
confidence: 50%
See 1 more Smart Citation
“…However, there is potential confusion over the relationship between habitat and/or locomotor preference and olecranon length. It has been argued that more terrestrial monkeys have shorter olecranons than do arboreal species [23,44,49], but in the present study, this trend is reversed, with 'forest arboreal' specimens having relatively short olecranons, in contrast to the longer olecranons of the 'open mixed' and 'open terrestrial' specimens, as well as T. oswaldi (tables 13, 16). To investigate this further, olecranon length was divided by both ulna length (OLUL) and ulna length minus styloid process length (OLUL2) (table 16).…”
Section: Eltoncontrasting
confidence: 50%
“…Jolly [44] argued that a short process relative to ulna length allows for full extension of the elbow, increasing the length of the forelimb during a stride, therefore being beneficial in terrestrial animals. In contrast, a longer process may be found in arboreal primates because it allows for increased forelimb power when the forelimb is habitually flexed [49]. However, Ciochon [24] found that in large-bodied papionins which have a posteriorly inclined olecranon, a relatively long olecranon would increase the mechanical advantage of the triceps at full extension of the elbow.…”
Section: Eltonmentioning
confidence: 93%
“…The olecranon process is relatively longer in highly quadrupedal cercopithecoids and platyrrhines compared to suspensory anthropoids (Jolly, 1967(Jolly, , 1972Harrison, 1989;Rose, 1993a;Drapeau, 2004). Contrasting results have been reported for relative length differences between arboreal and terrestrial quadrupeds (Rodman, 1979;Ciochon, 1993;Drapeau, 2004). An elongated olecranon process in arboreal quadrupeds has been related to increasing the power of the triceps brachii muscle during the bent-elbow posture performed during arboreal quadrupedalism, whereas the relatively shorter olecranon process in highly terrestrial quadrupeds has been explained as allowing fuller elbow extension when moving on the ground (Rodman 1979).…”
Section: Introductionmentioning
confidence: 93%
“…YD8-j (侧面垂直下降, sideways vertical descent), 身 体与支撑物的轴线垂直、处于身体下方的前后肢提 供主要的制动力; YD8-k (匍匐滑动, pronograde slide), 头部在前, 四肢紧握支撑物, 在光滑、倾斜 的树枝上被动下降, 身体通过前、后肢及其他部位 与支撑物之间的滑行而移动, 身体匍匐并与支持物 保持平行; YD8-l (摩擦支撑滑行, fire-pole slide), 臀 部在前, 在较粗的(直径>20 cm)垂直或近似垂直的 支撑物上被动滑行, 躯干直立, 四肢环抱支撑物, 依靠身体其他部分的微小滑动来下降, 并可通过前 肢来调整下降速率 (Hunt et al, 1996) (Tuttle, 1969;Stern & Oxnard, 1973;Jenkins & Fleagle, 1975;Fleagle, 1979;Rodman, 1979 (Gebo & Chapman, 1995a;Crompton, 1984;Dagosto, 1995;McGraw, 1998b;Garber, 1998)。灵长类位置行为在 季节性和具体地点两方面具显著差异。形成这种显 著差异的主要原因可能是进食、觅食策略以及食物 供给和分配的季节性变化 (Grand, 1972;CharlesDominique, 1977;Garber, 1980Garber, , 1984Crompton, 1984;Cant, 1987a;Boinski, 1989;McGraw, 1998a (Gebo, 1992;Gebo & Chapman, 1995b) Garber, 2007;Prates & Bicca-Marques, 2008)。 研 究表明, 体型大小、动作技能和生理状态的两性差 异以及个体发育是导致个体行为差异的重要因素 (Dunbar & Badam, 1998;Chatani, 2003;Prates & Bicca-Marques, 2008 …”
Section: 姿势行为(定义框架来源于unclassified